Analisis Yuridis Terhadap Kedudukan Keuangan Negara Dalam Penyertaan Modal Daerah Pada BUMD Berbadan Hukum Perseroan Terbatas - Muhammad Ridwan Lubis (Universitas Islam Sumatera Utara, 2018)
AbstractThe position of the State Finance as a separated asset which is included as regional capital in BUMD (Regional Owned Enterprises) incorporated as a limited liability company becomes the property of BUMD Persero and disconnected from the State / Regional Finance so that if the BUMD loses in carrying out its activities. If the loss is caused by an error or negligence of the Directors / management through examination and determination by a Public Accountant Consultant; consequently, the Directors / management can be prosecuted in civil but not criminal cases. BUMN (State-Owned Enterprises) /BUMD must submit to the State Finance Law because management and supervision are subject to the laws of a limited company, not following the APBN (Budget for State Revenues and Expenditures) or APBD (Budget for Regional Revenues and Expenditures) system. Keywords: BUMD, Public Money, Private Money